Seismotectonic characteristics of the area of Western Attica derived from the study of the September 7, 1999 Athens earthquake aftershock sequence - VOULGARIS, N.; PIRLI, M.; PAPADIMITRIOU, P.; KASSARAS, J.; MAKROPOULOS, K. (Bulletin of the Geological Society of Greece, 2001)
A detailed analysis of the aftershock sequence of the September 7, 1999 Athens earthquake was performed in order to define the fault planes activated during this sequence and study the tectonic regime of the area. Calculated fault plane solutions were verified by the composite solutions and the application of the principal parameters method. The combined results indicate a uniform tectonic status in the western part of the aftershock area, with normal faulting of WNW-ESE trend and an average dip of 60Ί and a more complex one in the eastern part, where the azimuths of the activated fault planes vary and a transverse antithetic fault is also active. This variation could possibly imply a variation of the local stress field.